Assessment of underground water resources of Gharo city, Sindh, Pakistan - Aamir Alamgir; Moazzam Ali Khan; Syed Shahid Shaukat; Salman Zubair (EQA, 2022)
This investigation focuses on the extent of public health quality of underground water available in Gharo city, Sindh Pakistan that represents a very poor socioeconomic profile. The city has a very limited piped water supply and the people mostly rely on well water. Underground water samples were collected from 28 different locations and the water quality was assessed through a deterministic sampling programme followed by an intense physicochemical and bacteriological analysis. The results of these analyses disclosed that the underground water is grossly polluted due to domestic and agricultural discharges. The problem is further aggravated by poor sanitation conditions. None of the water samples met the water quality criteria set by NSDWQ and WHO. The groundwater was found to be fecally contaminated and poses serious human health hazards. Effective measures are urgently required for water quality management in the city.